Aging-related episodic memory decline: are emotions the key? - Kinugawa, Kiyoka; Schumm, Sophie; Pollina, Monica; Depre, Marion; Jungbluth, Carolin; Doulazmi, Mohamed; Sebban, Claude; Zlomuzica, Armin; Pietrowsky, Reinhard; Pause, Bettina M.; Mariani, Jean; Dere, Ekrem (Frontiers in Behavioral Neuroscience, 2013)
Episodic memory refers to the recollection of personal experiences that contain information on what has happened and also where and when these events took place. Episodic memory function is extremely sensitive to cerebral aging and neurodegerative diseases. We examined episodic memory performance with a novel test in young (N = 17, age: 21 – 45), middle-aged (N = 16, age: 48 – 62) and aged but otherwise healthy participants (N = 8, age: 71 – 83) along with measurements of trait and state anxiety. As expected we found significantly impaired episodic memory performance in the aged group as compared to the young group. The aged group also showed impaired working memory performance as well as significantly decreased levels of trait anxiety. No significant correlation between the total episodic memory and trait or state anxiety scores was found. The present results show an age-dependent episodic memory decline along with lower trait anxiety in the aged group. Yet, it still remains to be determined whether this difference in anxiety is related to the impaired episodic memory performance in the aged group.